Clinical Characteristics and Prognosis of Hipec (Hyperthermic intraperitoneal Chemotherapy) plus surgery in different Histological types of Epithelial Ovarian Cancer - UK, Sajid Khan Durrani, FRCP; Rehman, Saeed ur; Heena, Humariya; Wani, Tariq; Malik, Azhar; Alobaisi, Yousef; Ali, Sheikh Zafar; Ahmed, Yasir A (Journal of Posthumanism, 2025)
Background: Ovarian Cancer also is known as the silent killer is the fifth most common cancer in females worldwide carrying a high mortality rate. In this study, we looked at clinical characteristics and outcomes of different stages and histopathological subtypes of epithelial ovarian cancer in 85 patients, following standard treatment with surgery and chemotherapy. Methods: Patients newly diagnosed with EOC between 2014 to 2017 who were treated with TAHBSO (150 TAHBSO in total with 15 HIPEC) were identified from a medical record maintained database. Surgery consisted of total hysterectomy, bilateral salpingo-oophorectomy, and total/partial omentectomy or HIPEC. The same chemotherapy was given adjuvant post-surgery as per standard guidelines. Results: The median age at the time of diagnosis for patients with Serous tumors was 55 years. Majority i.e. 94.1% of patients were high-grade serous type.The recurrence rate was 75 % for stage 4 patients who had surgery within 42 days of chemotherapy as opposed to 36.6 % of patients treated at an interval of greater than 42 days. This difference was not statistically significant despite slightly worse progression for patients who had a delay in surgery. Conclusions: Our study revealed a non –significant increased risk of recurrence with delaying chemotherapy for greater than 42 days for stage 4 disease while the delay in chemotherapy in stage 3c and lower ovarian cancer did not show any adverse outcome. We have identified the advanced stage of presentation of ovarian cancer being a more relevant factor for recurrence.